A framework for operationalising Aboriginal and Torres Strait Islander data sovereignty in Australia: Results of a systematic literature review of published studies. (March 2022) - Trudgett, Skye; Griffiths, Kalinda; Farnbach, Sara; Shakeshaft, Anthony
Summary: Background: Racial health disparities are only likely to be meaningfully improved by tailoring public health and clinical interventions to the specific needs of Indigenous people and their communities. Accurate tailoring relies on the availability of high-quality Indigenous-specific data. The potential benefits of increased availability of Indigenous data need to be balanced by efforts to ensure those data are collected and used appropriately. This paper identifies characteristics of Indigenous Data Sovereignty (IDS) principles and considers a framework for operationalisation. Methods: A PRISMA compliant search of the literature was undertaken, using methods detailed in the Cochrane Collaboration Handbook on Systematic Reviews of Health Promotion and Public Health Interventions (1). The search strategy comprised two steps: a search of 11 scientific electronic databases and five grey literature sources. The search was limited by date of publication (1 January 2000 to 1 December 2021). The following keywords and subject heading terms were used: (exp Aboriginal and Torres Strait Islander or Aborigin* or Torres Strait Island* or, Oceanic ancestry group) and (exp research or biomedical research or population surveillance or translational medical research or, research design) and (exp data or datasets or data collection or data management or health surveys or information dissemination or, intellectual property) and (exp self-determination or ownership or control or access or possession or OCAP or sovereignty or, ethics) and, (exp Australia). IDS principles: (i) ownership; (ii) control; (iii) accessibility; (iv) custodianship; (v) accountability to Indigenous people; (vi) amplify Community voice; (vii) relevant and reciprocal; and (viii) sustainably self-determining. Using standard data extraction forms, we examined relevant Australian studies to identify key characteristics and frequency with which they cited IDS principles. These findings were consolidated into an operationalisation framework. Findings: 34 relevant Australian published studies were identified. The most frequently cited IDS principles were Accountability to Aboriginal and Torres Strait Islander peoples and sustainably self-determining. The least frequently cited principle was Access. A framework to operationalise IDS principles is proposed that is both standardised internationally and able to be tailored to the diverse contexts of Indigenous peoples. Interpretation: IDS is emergent in Australia and there is a clear need to establish an agreed set of International IDS principles and a framework for their operationalisation and contextualisation across diverse Indigenous communities and contexts. Funding: This research project is funded through an Australian Research Council (ARC) Discovery Grant from 2017 to 2022. The National Drug and Alcohol Research Centre (NDARC) is funded by the Australian Government Department of Health . The 1st author (ST) is supported by a scholarship co-funded by NDARC and the Lowitja Institute.